The anxiety symptoms among chronic kidney disease patients who undergo hemodialysis therapy - Shahrul Rahman; Rangga Pradido (International Journal of Public Health Science (IJPHS), 2020)
Unresolved anxiety can lead to some impact on which a person tends to have a negative assessment of the meaning of life, decreased quality of life, emotional changes such as chronic depression and psychosis disorders. The general objective in this research is to find out the symptoms of anxiety symptoms of chronic kidney disease patients undergo hemodialysis. This research employed cross sectional design. This study used non-probability sampling type quota sampling. Sample was calculated using the Slovin formula obtained a sample size of 171. The proportion of patient with chronic kidney disease treated with hemodialysis based on the anxiety level resulting mild anxiety (86.5%) and moderate anxiety (13.5%). There are symptoms of anxiety symptoms in patients with chronic kidney disease undergoing hemodialysis.